A non-gradient approach for three dimensional topology optimization - Nguyen, Minh Ngoc; Thanh Nguyen, Nha; Tran, Minh Tuan (Vietnam Journal of Science and Technology, 2021)
The present work is devoted to the extension of the non-gradient approach, namely Proportional Topology Optimization (PTO), for compliance minimization of three-dimensional (3D) structures. Two schemes of material interpolation within the framework of the solid isotropic material with penalization (SIMP), i.e. the power function and the logistic function are analyzed. Through a comparative study, the efficiency of the logistic-type interpolation scheme is highlighted.  Since no sensitivity is involved in the approach, a density filter is applied instead of sensitivity filter to avoid checkerboard issue